2022
DOI: 10.1055/s-0042-1757885
|View full text |Cite
|
Sign up to set email alerts
|

Lung Cancer Screening

Abstract: Lung cancer is a leading cause of cancer death in the United States and globally with the majority of lung cancer cases attributable to cigarette smoking. Given the high societal and personal cost of a diagnosis of lung cancer including that most cases of lung cancer when diagnosed are found at a late stage, work over the past 40 years has aimed to detect lung cancer earlier when curative treatment is possible. Screening trials using chest radiography and sputum failed to show a reduction in lung cancer mortal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
17
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 25 publications
(20 citation statements)
references
References 67 publications
0
17
0
Order By: Relevance
“…Suitability of a screening program depends on the selection of a target risk population that would benefit from screening, the accuracy of the screening test, its frequency and duration, as well as the economic burden and adverse effects [ 24 ]. Radiation exposure is one of the major harms associated to LCS.…”
Section: The Problem Of Radiation Exposure In Lung Cancer Screeningmentioning
confidence: 99%
“…Suitability of a screening program depends on the selection of a target risk population that would benefit from screening, the accuracy of the screening test, its frequency and duration, as well as the economic burden and adverse effects [ 24 ]. Radiation exposure is one of the major harms associated to LCS.…”
Section: The Problem Of Radiation Exposure In Lung Cancer Screeningmentioning
confidence: 99%
“…The National Lung Screening Trial demonstrated a significant reduction in mortality with screening based on age and history of tobacco exposure [24]. LDCT is currently recommended by the United States Preventative Services Task Force for patients between the ages of 50 and 80, with at least a 20 pack-year smoking history and who are currently smoking or have stopped within the last 15 years [25]. The use of LDCT has been shown to detect lung cancers at earlier stages once screening programs are implemented [26].…”
Section: Workupmentioning
confidence: 99%
“…the last 15 years [25]. The use of LDCT has been shown to detect lung cancers at earlier stages once screening programs are implemented [26].…”
Section: Workupmentioning
confidence: 99%
“…Lung cancer is one of the common malignant cancers worldwide (Lee and Kazerooni, 2022). There are about 236,740 new cases of lung cancer and about 130,180 deaths from this disease in the United States (Siegel et al, 2022).…”
Section: Introductionmentioning
confidence: 99%